Mechanical Behaviour of Titanium Oxide-Coated Vessel Stents - Min, Zhonghua; Huang, Nan; Liu, Hengquan; Zhang, Qinyong (Asian Journal of Chemistry, 2014)
Vascular vessel stents were coated with titanium oxide (Ti-O) by a physical vapor deposition method. The composition, coating thickness and mechanical behaviour of the coating were investigated during stent compression and dilatation. The surface area and thickness of the Ti-O coating were calculated using known parameters. The composition of the coating was characterized via energy dispersive X-ray spectroscopy. The mechanical behaviour of the coating was investigated during stent deformation, particularly in regions experiencing high stress during compression or expansion. Results show that the Ti-O coating is smooth and uniform. There were no cracks or delaminations on the stent surface after dilation by angioplasty, indicating sufficient adhesion of the Ti-O coating to the stent.